1963
DOI: 10.1073/pnas.49.5.748
|View full text |Cite
|
Sign up to set email alerts
|

Cohesion of Dna Molecules Isolated From Phage Lambda

Abstract: Aggregation of DNA is often suspected but seldom studied. In phage lambda we found a DNA that can form characteristic and stable complexes. A first account of them is given here.Materials and Methods.-DNA was extracted from a clear-plaque mutant (genotype cb+) of phage lambda' by rotation2 or shaking' with phenol. Sodium dodecylsulfate, ethylenediaminetetraacetate, citrate, or trichloroacetate was sometimes included in the extraction mixture without effect on the properties of the DNA. Phenol was removed by di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
58
0

Year Published

1966
1966
2013
2013

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 229 publications
(60 citation statements)
references
References 8 publications
2
58
0
Order By: Relevance
“…Communicated by John N. Couch, September 30,1970 Abstract. In an exceptionally well-defined first cleavage metaphase in a sectioned egg of Polychoerus carmelensis all 34 (2n) chromosomes were present in a single 8-micron section, and it was possible to identify the homologous chromosomes derived from the two parent gametes.…”
mentioning
confidence: 99%
“…Communicated by John N. Couch, September 30,1970 Abstract. In an exceptionally well-defined first cleavage metaphase in a sectioned egg of Polychoerus carmelensis all 34 (2n) chromosomes were present in a single 8-micron section, and it was possible to identify the homologous chromosomes derived from the two parent gametes.…”
mentioning
confidence: 99%
“…Cairns (4) observed in his well known autoradiograms that the DNA in an E. coli cell is arranged in one long circular unit. Hershey, Burgi, and Ingraham (5) found that the linear DNA from coliphage lambda had sticky ends which could be induced to form circular DNA. In the same year Dulbecco and Vogt (6) and Weil and Vinograd (7) showed that the DNA from the tumor virus, polyoma, was in the form of covalently closed circular duplex molecules.…”
mentioning
confidence: 99%
“…This paper reports our findings that partially purified ligase from E. coZi C641 catalysed the covalent closure of "Hershey" circles [2] of h DNA only in the presence of ATP and that NAF was not required for the reaction. The requirement for ATP was lost during purification of the ligase, and after the final stage of purification NAITcould be shown to increase the amount of covalently closed product.…”
Section: Introductionmentioning
confidence: 84%